Odpowiedź :
Odpowiedź:
c) 5 i 4/9 - 3 i 5/8= 5 i 32/72-3 i 45/72= 4 i 104/72- 3 i 45/72= 1 i 59/72
d) 11/12 *4/5 ( skracamy 12 i 4 przez 4)= 11/3 *1/5= 11/15
e) 2/3 : 8/7= 2/3 * 7/8 ( skracamy 2 i 8 przez 2)= 1/3*7/4= 7/12
f) 1 i 3/5 *2 i 1/4= 8/5 *9/4( skracamy 8 i 4 przez 4)= 2/5*9= 18/5= 3 i 3/5
Szczegółowe wyjaśnienie:
Odpowiedź:
5 i 4/9 - 3 i 5/8 = 5 i 32/72 - 3 i 45/72 = 4 i 104/72 - 3 i 45/72 = 1 i 59/72
11/12 * 4/5 = 11/15 skracamy 12 i 4 przez 4
2/3 : 8/7 = 2/3 * 7/8 = 7/12 skracamy 2 i 8 przez 2
1 i 3/5 * 2 i 1/4 = 8/5 * 9/4 = 18/5 = 3 i 3/5 skr 8 i 4 przez 4